Elite networks and the transregional dimension of authoritarianism: Sino-Emirati relations in times of a global pandemic - Gurol-Haller, Julia; Zumbrägel, Tobias; Demmelhuber, Thomas (Journal of contemporary China, 2023)
Scholarly debates on Chinese foreign policy in the Middle East and the international dimension of authoritarianism have gained momentum since Beijing’s Belt and Road Initiative (BRI) in 2013. At the same time, the global pandemic provided a window of opportunity to autocrats worldwide to fine-tune their modes of surveillance for the sake of regime survival. This article deconstructs Sino-Emirati relations in the field of digital surveillance. Inspired by Social Network Theory, we explore three transregional public-private elite networks as multipliers for the traveling of authoritarian practices. We show that authoritarian diffusion under the umbrella of fighting the pandemic is not spatially bound to geographical proximity or other structural similarities but rather a global phenomenon that state and non-state actors reproduce. (J Contemp China/GIGA)
Keywords: China; Vereinigte Arabische Emirate